2.09 Ga old eclogites in the Eburnian-Transamazonian orogen of southern Cameroon: significance for palaeoproterozoic plate tectonics - Loose, Denny; Schenk, Volker (Precambrian research, 2018)
Lenses of retrogressed eclogites occur in a 100km wide zone of the Nyong Complex, a remnant of the Eburnian-Transamazonian orogen, marking a Palaeoproterozoic suture between the Congo and São Francisco Cratons. The eclogites show trace element pattern (depleted in LREE) similar to those of mid-ocean ridge basalts, indicating that the precursor melts formed in a depleted mantle source and the eclogites formed from oceanic crust. Despite numerous plagioclase ‘exsolutions’ up to 25 mol% jadeite component is preserved in omphacite and points to minimum pressures of 16kbar at c. 800°C. Pressures may have been 18-20kbar as indicated by estimated compositions of peak omphacite. The age of eclogite metamorphism has been constrained by U-Pb SHRIMP dating of zircon at 2093±45 Ma. The eclogites are associated with 2.05 Ga old charnockites and mafic granulites containing textures characteristic for near-isobaric cooling. These rocks may represent the plate above a subduction zone in which the eclogites were tectonically emplaced. With an age of 2.09 Ga the eclogites of the Nyong Complex are older than other subduction related Palaeoproterozoic eclogites of the Ubendian (1.88 Ga) and Usagaran belts (2.0 Ga) at the southern border of the Tanzania Craton. They are also older than eclogites in the Belomorian province (1.9 Ga; Russia) and thus represent the oldest known eclogites outcropping in an orogenic belt. The African eclogites (all with MORB chemistry) indicate that during the formation of the Nuna supercontinent the Palaeoproterozoic oceanic lithosphere around the Congo-Tanzania Craton was thick, cold and rigid enough to become subducted similar to cold oceanic lithosphere in the modern plate tectonic regime. However, apparent geothermal gradients of 12-14°C/km for the Palaeoproterozoic eclogites are higher than those of Neoproterozoic and Phanerozoic eclogites and are interpreted as the result of warm subduction in a hotter Palaeoproterozoic Earth.
Available online 24 October 2017
Gesehen am 09.07.2019